Prevalence and Clinical Characteristic of Chloroquine and Hydroxychloroquine Maculopathy in Patients at Sukhothai Hospital - Yoosamran, Saralai (Journal of Health Sciences Sukhothai hospital, 2026)
Background: Chloroquine and Hydroxychloroquine can cause maculopathy that can lead to incurable and irreversible visual impairment in patients who received these drugs for a long time. Regular screening for Chloroquine- and Hydroxychloroquine-induced maculopathy in patients receiving these drugs is important to reduce the risk of permanent vision loss. Objective: To evaluate prevalence and clinical characteristics of Hydroxychloroquine (HCQ) and Chloroquine (CQ) maculopathy in patients at Sukhothai hospital. Methods: A Retrospective descriptive study of 222 patients who received either Chloroquine (CQ) or Hydroxychloroquine (HCQ) from 1st January 2019 – 31st December 2020 at Sukhothai hospital. Medical records were reviewed to collect details regarding age, body weight, daily doses of CQ or HCQ, duration of treatment and eye examination records consisting of VA, Ishihara test, time domain optical coherence tomography (TD-OCT), computed tomography visual fields (CTVF), and fundus photography. Results: 180 patients who received CQ or HCQ and were screened for maculopathy were included. Mean age was 60.19 years (SD 11.87). Diagnoses were Lupus 18.75% and Rheumatoid arthritis 81.25%. From 180 patients, maculopathy was found in 8.89% (Chloroquine 17.02%, Hydroxychloroquine 0.6%). 56.25% received CQ or HCQ for 5-10 years, 43.75% for 1-5 years. No maculopathy was found in patients who received the drug less than 1 year. 62.50% received daily dose in high risk range. Most patients were moderate visual impairment 43.75%, no visual impairment 31.25%, and blindness 6.25%. All patients had color defect. CTVF and TD-OCT showed Perifoveal pattern 43.75%, Parafoveal pattern 31.25%, and Mixed pattern 25%. Only 2 of 16 showed Bull’s eye pattern on fundus photography. Conclusion: The prevalence of Chloroquine (CQ) and Hydroxychloroquine (HCQ) induced maculopathy in patients at Sukhothai hospital is 8.89% (prevalence of CQ maculopathy 17.02%, HCQ maculopathy 0.6%). Most patients received CQ or HCQ for more than 5 years and the shortest duration that caused maculopathy was 1 year 6 months. Almost all cases received high-risk doses for toxicity. Visual acuity was mostly moderate visual impairment and all patients had a color defect. CTVF and TD-OCT showed Perifoveal pattern of maculopathy predominating over Parafoveal pattern.